Paleoenvironments and Sequence Stratigraphy of the Turonian-Lower Campanian Succession at Majnoon Oil Field, Southern Iraq - D. Gayara, Ali; H. Al khaykanee, Mustafa (Iraqi Journal of Science, 2023)
The Turonian-Lower Companian succession at Majnoon Oil Field is represented by the Khasib, Tanuma, and Saadi formations. Four major paleoenvironments were recognized within the studied succession, there are: Shallow open marine environment, shoal environment, deep marine environment, and basinal environment. They reflect deposition on a carbonate platform of homoclinal ramp setting. The studied succession represents two second order supersequences (A) and (B). Supersequence (A) includes both the Khasib and Tanuma formations. The Saadi Formation represents cycle (B). These second order cycles can be divided each into two third order cycles, This subdivision may reflect the effect of eustacy being the major controlling factor of cycles development in the area of very gentle slope and low rate of subsidence. Further subdivision into fourth order cycles may reflect the minor relative sea level fluctuations due to the change in gradient in the vicinity of the shoalbodies where the water depth is lower and sensitive to any subtle changes in relative sea level.